2008
DOI: 10.2134/agronj2007.0204
|View full text |Cite
|
Sign up to set email alerts
|

Year, Region, and Temperature Effects on the Quality of Minnesota's Soybean Crop

Abstract: Bulk commodity soybean [Glycine max (L.) Merr.] can now be sourced with great specifi city through rail and container purchases. Th e objective of this study was to determine whether analyses of farmer-grown soybean seed samples could detect significant regional diff erences in soybean quality traits. Th rough analysis of 2706 farmer volunteered soybean samples representing harvests from 2003-2005, we found signifi cant year and region eff ects on seed quality. An independent variable, temperature during seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 23 publications
4
26
1
Order By: Relevance
“…It should be noted that genetic improvement during the last 35 yr may be the reason for the discrepancy regarding the protein response to temperature. Similar results were observed by Naeve and Huerd (2008), who found that oil concentrations increased due to increasing temperature during seed fill in Minnesota. No effect on protein was observed in their study.…”
Section: Temperature × Maturity Group Effectssupporting
confidence: 88%
See 1 more Smart Citation
“…It should be noted that genetic improvement during the last 35 yr may be the reason for the discrepancy regarding the protein response to temperature. Similar results were observed by Naeve and Huerd (2008), who found that oil concentrations increased due to increasing temperature during seed fill in Minnesota. No effect on protein was observed in their study.…”
Section: Temperature × Maturity Group Effectssupporting
confidence: 88%
“…Wolf et al (1982) reported increased protein and oil content, increased oleic acid, and decreased linolenic and linoleic acids as the temperature during seed fill was increased. More recently, Naeve and Huerd (2008) collected field grain samples from different growing regions within Minnesota and found that oil concentrations increased by 6.6 g kg -1 o C -1 during seed fill, but protein was not affected. The temperature during seed fill explained more variation in oil content than a specific year did.…”
mentioning
confidence: 99%
“…seed fi ll. Moreover, Naeve and Huerd (2008) found a significant positive linear response of oil + protein to temperature during the seed-fi lling period in farm-fi eld samples in Minnesota. These apparently confl icting results highlight the great complexity of the environmental variables that determine the protein concentration, which could also probably increase interactions, generating different mega-environments, with the consequent opportunity for specifi c adaptations (Dardanelli et al, 2006).…”
Section: Discussionmentioning
confidence: 88%
“…After the joint analysis of the experiments, analyses of environmental stratification and of adaptability and stability of genotypes were performed according to the following methods: Wricke (1965), Annicchiarico (1992), Lin & Binns (1988) modified by Cruz & Carneiro (2003), and centroid (Nascimento et al, 2009). The proportions of simple and complex mean squares for the interaction between genotypes and pairs of environments (MSGxEjj') were calculated according to Robertson (1959) and Cruz & Castoldi (1991).…”
Section: Fortymentioning
confidence: 99%
“…The differential response of soybean genotypes to changes in environments is often evaluated by estimating the interaction effects of genotypes x locations, genotypes x years, genotypes x locations x years, and genotypes x sowing dates, although these effects are complex and the biological meaning of the contrasts is hard to explain biologically (Albrecht et al, 2008;Naeve & Huerd, 2008;Zhe et al, 2010;Barbosa et al, 2011). After estimating the interaction effects, genotype performance against environmental variations should be evaluated by analyses of adaptability and stability, which allow for identifying cultivars with predictable or responsive behavior to environmental variations, in specific or broad conditions (Cruz & Carneiro, 2003).…”
Section: Introductionmentioning
confidence: 99%